PERFORMANCE OF COCKEREL CHICKSFED DIETS CONTAINING GRADED LEVELS OF CASHEW (Anarcadium occidentale L.) PULP MEAL - Oyewole, B. O.; Joseph, M.; Ahutu, I. A. (FUDMA JOURNAL OF SCIENCES, 2023)
One hundred and fifty (150) day-old cockerel chicks were used in a five week feeding trial to evaluate five (5) diets, in which cashew pulp meal (CPM) replaced 0%, 10%, 20%, 30% and 40% of maize in T0, T1, T2, T3 and T4, respectively. Each treatment had thirty (30) cockerel chicks, with 10 birds per replicate. All performance parameters measured were significantly different (P<0.05). Final weight (FW), daily weight gain(DWG), daily feed intake (DFI), feed conversion ratio (FCR), mortality, feed cost/kg gain (FC/kg gain) and cost of 1kg feed ranged from 300.00-352.68g, 7.21-9.03g, 23.01-26.58g, 2.74-3.50, 3.33-13.33%,N361.32-N439.60 and N115.43-N135.46, respectively. It was concluded that inclusion of cashew pulp meal (CPM) in the diets of cockerel chicks depressed weight gain, live weight and resulted in poorer FCR. However, the progressive inclusion of cashew pulp meal in the diet resulted in concurrent reduction in the cost/kg of feed, and the most economic production when 30% maize was replaced by cashew pulp meal. Based on the results of this feed trial, replacement of maize by CPM in cockerel chicks’ diet may prolong the attainment of market weight of birds, because of depressed performance.